(untitled) (Journal SCIENCEVOLUTION, 2024)
Climate change is affecting water regulation by modifying precipitation patterns, reducing water availability, melting glaciers and raising sea levels, which is why we have been experiencing frequent and prolonged droughts, leading to a decrease in water availability, directly affecting agriculture, which is one of the most important sectors of the economy. For this reason, it is necessary to reflect on the economic value of the water regulation service, considering the economic, social and environmental benefits that contribute to the welfare of the population; for this purpose, a systematic review of the primary studies of South American countries was carried out. In the case of geophysical information, information from meteorological stations neighboring the basin under study was reviewed. The results show that the economic value of water is 0.55 soles (0.15 USD) per cubic meter of water; on the other hand, a minimum temperature increase of 7.55 °C is predicted for 2050 and the economic value of water would be 1.16 soles (0.32 USD) per cubic meter of water.